Generation Friends : an inside look at the show that defined a television era - Austerlitz, Saul (Dutton, an imprint of Penguin Random House, 2019)
In September 1994, six friends sat down in their favorite coffee shop and began bantering about sex, relationships, jobs, and just about everything else. A quarter of a century later, new fans are still finding their way into the lives of Rachel, Ross, Joey, Chandler, Monica, and Phoebe, and thanks to the show<U+2019>s immensely talented creators, its intimate understanding of its youthful audience, and its reign during network television<U+2019>s last moment of dominance, Friends has become the most influential and beloved show of its era. Friends has never gone on a break, and this is the story of how it all happened. Noted pop culture historian Saul Austerlitz utilizes exclusive interviews with creators David Crane and Marta Kauffman, executive producer Kevin Bright, director James Burrows, and many other producers, writers, and cast members to tell the story of Friends<U+2019> creation, its remarkable decade-long run, and its astonishing Netflix-fueled afterlife. Readers will go behind the scenes to hear from the people who were present as the show was developed and cast, written and filmed. There will be talk of trivia contests, prom videos, trips to London, Super Bowls, lesbian weddings, wildly popular hairstyles, superstar cameos, mad dashes to the airport, and million-dollar contracts. They<U+2019>ll also discover surprising details<U+2014>that Monica and Joey were the show<U+2019>s original romantic couple, how Danielle Steel probably saved Jennifer Aniston<U+2019>s career, and why Friends is still so popular that if it was a new show, its over-the-air broadcast reruns would be the ninth-highest-rated program on TV. The show that defined the 1990s has a legacy that has endured beyond wildest expectations. And in this hilarious, informative, and entertaining book, readers will now understand why.